Optimal employment contracts and the returns to monitoring in a principal‐agent context - BAIMAN, STANLEY; MAY, JERROLD H.; MUKHERJI, ARIJIT (Contemporary Accounting Research, 1990)
Abstract. In this paper we study a two‐person firm consisting of a principal and an agent. The principal hires the agent to provide some input into the production process. The output of the production process is determined by the agent's input and an exogenous state realization. Subsequent to joining the firm, but prior to choosing his input, the agent privately observes the state realization. The principal employs an imperfect monitoring system that publicly reports on the state realization. Our purpose in studying this model is to better understand the effects of monitoring on the design of the optimal employment contract and the determinants of the value of monitoring in a model with asymmetric information. Résumé. Les auteurs étudient une entreprise constituée de deux personnes, un mandant et un mandataire. Le mandant embauche le mandataire pour sa contribution au processus de fabrication. Le résultat du processus de fabrication est déterminé par la contribution du mandataire et par la réalisation d'un état exogène. Après s'être joint à l'entreprise, mais avant de déterminer quelle sera sa contribution, le mandataire observe, en privé, la réalisation de cet état exogène. Le mandant a recours à un système de suivi imparfait qui fait le point, à l'intention du public, sur la réalisation de l'état en question. L'étude de ce modèle permet une meilleure compréhension des conséquences du suivi sur la nature de contrat d'emploi optimal et des déterminants de la valeur du suivi dans un modèle caractérisé par une information asymétrique.